Regulatory and legal provision of banking sector capitalization in conditions of macroeconomic instability - Alina Yefimenko (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет, 2022)
The article summarizes the regulatory and legal provision of bank capitalization in conditions of macroeconomic instability using the example of Ukraine. The author systematizes the main approaches to determining the categories of legislation in the field of capitalization based on a review of publications by foreign and domestic scientists. The purpose of the article is to analyze the regulatory and legal provision of capitalization of the banking sector in the example of Ukraine and assess the existing gaps in the legislative framework. Within the framework of the article, a bibliometric analysis was carried out for the systematization of scientific works in the field of regulatory support of bank capitalization. The following research tools were used in the article: methods of analysis and synthesis, grouping, bibliographic analysis, comparison method, etc. The following categories of regulatory support for bank capitalization have been identified the primary State Law, State Laws, the main Central Bank Law and regulatory acts developed in accordance with the specifics of the bank's activities. The article identifies the main gaps in legislation at various levels of banking activity. From the NBU's point of view, the level of capital adequacy is characterized by banks' compliance with the specified standards H1 and H2. At the international level, these indicators are covered in the standards of the Basel Committee on Banking Regulation (Basel I, II, III). Several external and internal factors affect banks' implementation of the specified regulations. Macroeconomic factors include social, geopolitical factors, technological factors and national indicators. This determines the need for banks to consider fluctuations in GDP and incomes of the population when developing a resource policy, as well as implementing national legislation. Also, banks need to develop and implement appropriate action plans for negative scenarios of economic growth and population impoverishment.